Maintenance of Blood-Brain Barrier Integrity in Hypertension: A Novel Benefit of Exercise Training for Autonomic Control - Buttler, Leila; Jordão, Maria T.; Fragas, Matheus G.; Ruggeri, Adriana; Ceroni, Alexandre; Michelini, Lisete C. (Frontiers in Physiology, 2017)
The blood-brain barrier (BBB) is a complex multicellular structure acting as selective barrier controlling the transport of substances between these compartments. Accumulating evidence has shown that chronic hypertension is accompanied by BBB dysfunction, deficient local perfusion and plasma angiotensin II (Ang II) access into the parenchyma of brain areas related to autonomic circulatory control. Knowing that spontaneously hypertensive rats (SHR) exhibit deficient autonomic control and brain Ang II hyperactivity and that exercise training is highly effective in correcting both, we hypothesized that training, by reducing Ang II content, could improve BBB function within autonomic brain areas of the SHR. After confirming the absence of BBB lesion in the pre-hypertensive SHR, but marked fluorescein isothiocyanate dextran (FITC, 10kD) leakage into the brain parenchyma of the hypothalamic paraventricular nucleus (PVN), nucleus of the solitary tract and rostral ventrolateral medulla during the established phase of hypertension, adult SHR and age-matched WKY were submitted to a treadmill training (T) or kept sedentary (S) for 8 weeks. The robust FITC leakage within autonomic areas of the SHR-S was largely reduced and almost normalized since the 2nd week of training (T2). BBB leakage reduction occurred simultaneously and showed strong correlations with both decreased LF/HF ratio to the heart and reduced vasomotor sympathetic activity (power spectral analysis), these effects preceding the appearance of resting bradycardia (T4) and partial pressure fall (T8). In other groups of SHR-T simultaneously infused with icv Ang II or saline (osmotic mini-pumps connected to a lateral ventricle cannula) we proved that decreased local availability of this peptide and reduced microglia activation (IBA1 staining) are crucial mechanisms conditioning the restoration of BBB integrity. Our data also revealed that Ang II-induced BBB lesion was faster within the PVN (T2), suggesting the prominent role of this nucleus in driven hypertension-induced deficits. These original set of data suggest that reduced local Ang II content (and decreased activation of its downstream pathways) is an essential and early-activated mechanism to maintain BBB integrity in trained SHR and uncovers a novel beneficial effect of exercise training to improve autonomic control even in the presence of hypertension.